Curriculum theory and practice: A comparative literature review - Frank Angelo Pacala (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2023)
The curriculum has emerged over the past century from a simple list of subject-specific outcomes to an intricate and holistic set of experiences for students to grapple with. This comparative literature review discusses the research related to curriculum theory and practice. It draws upon a range of sources, from Mark K Smith’s article on Curriculum Theory and Practice, theoretical discussions of curriculum planning and evaluation to empirical studies of educational planning in varied contexts. The purpose of this research is to evaluate the Theory of Smith as compared to other related literature on curriculum theory and planning. This review discussed curriculum as a transmission of knowledge, a product, a process, and a praxis. The findings found that all approaches to curriculum development as a product of momentary articulations, as well as a dynamic process of collective becoming and reflective action. This paper found that most literature agrees with the theory of Smith. Therefore, this paper concluded that any type of school curriculum should be viewed as a combination of a product, process, and praxis.